Življenjske navade pacientov z arterijsko hipertenzijo v domačem okolju - Potočnik, Špela (Obzornik zdravstvene nege, 2012)
Introduction: Arterial hypertension is a disease of modern times, presenting an important socio-medical issue. It is a major cardiovascular disease risk factor. The prevalence of the disease increases with age, but may develop also within young adult population. Along with medication and other therapies, a modification of a lifestyle is of paramount importance. It largely depends on patients' motivation and treatment adherence. The aim of the study was to evaluate the lifestyle and identify cardiovascular risk factors that may affect prognosis and guide treatment of patients with arterial hypertension. Methods: A descriptive research method was used in the study conducted in April 2011. The data were obtained through a questionnaire, consisting of 22 closed-ended and 4 semi-open questions. Content analysis was used to process the data retrieved through semi-open questions. The questionnaire was designed so as to meet the specific research objectives. Participating in the study were 50 patients with arterial hypertension who visited their family doctor at the outpatient clinic Šoštanj within the time span given. Results: The results of the study show that the majority of survey respondents comply with general lifestyle recommendations. It was established that 70% of respondents do not smoke, 30% never drank alcohol, and 54% never used extra salt. Coffee, however, is consumed daily by 56% of respondents. The percentage of physically inactive (36%) and overweight respondents (76%) is, however, disturbing. Discussion and conclusion: Nurses and other health professionals play a crucial role in health education, focusing on prevention and promotion of healthy behaviour. Treatment can only be successful when patients are motivated and willing to actively participate in the treatment process.
Keywords: arterial hypertension; arterijska hipertenzija; blood pressure; bolniki; health education; krvni tlak; medicinske sestre; nurses; therapy; treatment; zdravljenje; zdravstvena vzgoja; življenjske navade